2016
DOI: 10.1159/000447837
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Modulates the Distribution of Connexin 43 in Epithelial Cells

Abstract: Background/Aims: The fact that ouabain has been identified as an endogenous substance, led us to inquire its physiological role in epithelial cells. Based on previous observations, we hypothesized that it influences processes related to cell contacts. Previously we have shown that nanomolar concentrations of ouabain up-regulate tight junctions, accelerate ciliogenesis, and increase gap junctional intercellular communication (GJIC). Given that silencing assays indicated that connexin 43 (Cnx43) is involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…As previously mentioned, Na-K-ATPase has been shown to be the receptor that transduces the action of cardiac glycosides in various physiological processes, and we have previously demonstrated that this also happens in the changes that ouabain induces on GJIC and TER of MDCK cells [36][37][38].…”
Section: Involvement Of Na-k-atpase In a The Effect Of Marinobufagenisupporting
confidence: 57%
See 1 more Smart Citation
“…As previously mentioned, Na-K-ATPase has been shown to be the receptor that transduces the action of cardiac glycosides in various physiological processes, and we have previously demonstrated that this also happens in the changes that ouabain induces on GJIC and TER of MDCK cells [36][37][38].…”
Section: Involvement Of Na-k-atpase In a The Effect Of Marinobufagenisupporting
confidence: 57%
“…us, we have demonstrated that ouabain influences Tight Junctions (TJ), as reflected by a significant increase in the Transepithelial Electrical Resistance (TER) and to an increased expression of claudins 2 and 4 [36]. It also induces, within minutes, Gap Junctional Intercellular Communication (GJIC) by promoting relocation of connexins 32 and 43 [37,38]. Ouabain 10 nM upregulates Adherens Junctions, enhancing the cellular content of E-cadherin, β-catenin, and c-catenin [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that ouabain promotes cell-to-cell contacts and cell proliferation in cultured cells (8, 9, 43). There is also evidence that ouabain affects embryonic growth and development in mammals, because offspring of mice treated with anti-ouabain antibodies have lower body weight (11) and ouabain supplementation to malnourished pregnant mice prevents adverse development of the kidney in the offspring (64).…”
Section: Discussionmentioning
confidence: 99%
“…S4A). Previous studies by Cereijido et al demonstrated that ouabain, when employed at a subsaturating concentration, plays a major role in regulating the permeability and composition of tight junctions (8,9,43). Furthermore, cell adhesion molecules play a significant role in cancer progression and metastasis, and many of the adhesive molecules phosphorylated in response to ouabain have been suggested as potential therapeutic targets in cancer (44,45).…”
Section: Ouabain Regulates Proteins Responsible For the Oscillatory Cmentioning
confidence: 99%
“…Previous studies demonstrated that binding of cardiotonic steroids such as ouabain to the sodium pump stimulates multiple kinase cascades [57]. Therefore, the effect of ouabain on the β 1 -β 1 interaction could be explained by the potential activation of some components from the signaling machinery that is known to modulate cell junctions such as TJs, AJs and GAP junctions [29,58]. We first screened for signaling proteins of the family of tyrosine kinases that were differentially activated compering between CHOβ 1 and CHO wild type cells.…”
Section: The β 1 -β 1 Adhesion Induced By Ouabain Depends On the Actimentioning
confidence: 99%